1998
DOI: 10.1152/ajpgi.1998.274.1.g122
|View full text |Cite
|
Sign up to set email alerts
|

Identification and localization of extracellular Ca2+-sensing receptor in rat intestine

Abstract: The extracellular calcium ([Formula: see text])-sensing receptor (CaR) plays vital roles in [Formula: see text] homeostasis, but no data are available on its expression in small and large intestine. Polymerase chain reaction products amplified from reverse-transcribed duodenal RNA using CaR-specific primers showed >99% homology with the rat kidney CaR. Northern analysis with a CaR-specific cRNA probe demonstrated 4.1- and 7.5-kb transcripts in all intestinal segments. Immunohistochemistry with CaR-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
149
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 21 publications
9
149
1
1
Order By: Relevance
“…Apart from human colon adenocarcinoma-derived cell lines such as Caco-2 (Kállay et al 1997) or T84 and HT-29 (Gama et al 1997), the presence of the CaR has been shown in normal rat small and large intestine (Gama et al 1997;Chattopadhyay et al 1998). In this study we were able to show that human colon mucosal cells also express the CaR at the message and protein level (cf.…”
Section: Discussionsupporting
confidence: 51%
“…Apart from human colon adenocarcinoma-derived cell lines such as Caco-2 (Kállay et al 1997) or T84 and HT-29 (Gama et al 1997), the presence of the CaR has been shown in normal rat small and large intestine (Gama et al 1997;Chattopadhyay et al 1998). In this study we were able to show that human colon mucosal cells also express the CaR at the message and protein level (cf.…”
Section: Discussionsupporting
confidence: 51%
“…Epithelial cells along the entire length of the intestine express the CaSR (8-10); however, the functions of this receptor in the gastrointestinal tract are only beginning to be understood (11). The CaSR has been identified on both the luminal and basolateral sides of human (10,12) and rat colonocytes (8,10), and receptors on both sides of this polarized epithelium can be activated by extracellular calcium and other polycations like spermine (9,10). CaSR activation of G q in colonocytes (10), as well as other cell types (2), results in a rise in intracellular Ca 2ϩ via activation of phospholipase C (PLC), formation of IP 3 , and subsequent Ca 2ϩ release from IP 3 -sensitive cytosolic stores (10).…”
mentioning
confidence: 99%
“…The CaR, a G protein-coupled receptor, is best known and understood for its control of PTH synthesis and secretion in response to changes in Ca, Mg, Sr, and La (17,18). CaRs are distributed along most of the gastrointestinal tract, from the stomach to the large intestine (23,28). The physiologic role of CaRs is the maintenance of constant blood Ca 2 + levels (1.1-1.3 mM) through continuous adjustments of PTH release from the parathyroid chief cells, which are highly sensitive to the slightest changes in extracellular Ca ion concentrations (17,18).…”
Section: Discussionmentioning
confidence: 99%